Breaking Down Greek Nominal Stems: Theme and Nominalizer Exponents - Giorgos Markopoulos (Languages)
This article focuses on the right edge of nominal stems in Greek and aims to show that stem-final segments should be analyzed as distinct morphological constituents. Two types of such constituents are identified. On the one hand, stem endings such as -a(ð), -i(ð), and -a(t) have a predictable distribution, as they are found in nouns with specific morphosyntactic properties and stress patterns. On the other hand, stem endings like -o, -a, and -i cannot function as predictors of the morphosyntactic status of the noun, although they may convey information about its stress position. The distinction between the two constituent categories is captured through an analysis couched within Distributed Morphology. Specifically, it is proposed that stem endings of the first category function as nominalizer exponents, while those of the second category serve as exponents of a Theme node, which is inserted post-syntactically and bears no grammatical features. The allomorphic variation exhibited by these exponents is accounted for by means of a phonological analysis based on Gradient Harmonic Grammar. The proposed approach is shown to capture empirical generalizations that have been overlooked in traditional grammatical descriptions and theoretical analyses based on multiple stem allomorphs.